PEMANFAATAN MEDIA INTERNAL ENERGIA WEEKLY DALAM MEMBANGUN KOMUNIKASI EFEKTIF OLEH HUMAS PT. PERTAMINA (PERSERO) - R. Agni Najwa Madenda; Santoso, Hudi (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study aims to analyze the utilization of the internal media Energia Weekly by the Public Relations Division of PT Pertamina (Persero) in building effective internal communication within the company. Using a descriptive qualitative approach, data were collected through interviews, observations, literature studies, and internal document analysis. The findings indicate that Energia Weekly plays a crucial role as a two-way communication medium that supports the dissemination of corporate policies while serving as a participatory platform for employees. The media successfully enhances employee engagement, loyalty, and the delivery of corporate values through its interactive sections. A SWOT analysis reveals the strengths of Energia Weekly in fostering engagement and strengthening corporate culture, although challenges such as limited distribution and outdated content remain. Opportunities lie in digital transformation and increased employee involvement, while the main threats include shifting information consumption preferences and the risk of internal data leaks. Thus, Energia Weekly is considered a strategic tool that supports effective internal communication and enhances the company’s overall corporate image.